44. EVALUATION OF THE TREATMENT EFFECT OF KNEE OSTEOARTHRITIS WIND-COLD-DRY SYMPTOMS WITH LIVER-KID DEFICIENCY BY THE MEDICINE "DOC HOAT TANG KI SINH" COMBINED WITH ELECTRIC PULSE (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the treatment effect of osteoarthritis of the knee with the cold and dampness syndrome accompanied by the deficiency of the liver and kidney by the prescription “Du Huo Ji Sheng Tang” combined with electric pulse and to describe some unwanted effects of the treatment method.Method: 60 patients regardless of gender and occupation were diagnosed with osteoarthritis of the knee according to the criteria of the American College of Rheumatology (ACR) 1991 and the disease with the cold and dampness syndrome accompanied by the deficiency of the liver and kidney according to traditional medicine. Control group: Including 30 patients using the prescription “Du Huo Ji Sheng Tang” in the form of decoction, taking 1 dose per day, boiled into 2 bags, divided into 2 times per day, taken after breakfast and dinner. Research group: Including 30 patients using the medicine " Du Huo Ji Sheng Tang " in the form of decoction, drinking 1 decoction per day, divided into 2 bags, divided into 2 times per day, drinking after breakfast and dinner combined with Electrotherapy in the knee joint area, 1 time per day, for 20 minutes (except Saturday and Sunday). Treatment regimen: Two groups used the medicine continuously for 20 days.Results: Both groups after treatment had a better WOMAC total score, knee range of motion, and heel-buttock index than before treatment (p < 0.05) with the research group having better treatment than the control group.Conclusion: The method of treating knee osteoarthritis with wind-cold-dampness and kidney deficiency using the medicine "Doc hoat tang ki sinh" combined with electrotherapy gave good clinical results and currently there have been no unwanted effects in clinical and some paraclinical indicators.
Keywords: Knee osteoarthritis; electrotherapy; Du Huo Ji Sheng Tang